PEMANFAATAN LABU KUNING DALAM PEMBUATAN PERMEN JELLY DENGAN PENAMBAHAN RUMPUT LAUT - Dedy Insan; Netti Herawati; Evy Rossi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this study was to obtain the ratio of pumpkin and seaweed which was selected in the manufacture of jelly candy according to chemical and organoleptic quality. This research was conducted by using Completely Randomized Design (CRD) with five treatments and three replications. The treatments in this study were LKRL1 (ratio of pumpkin:seaweed 66:34), LKRL2 (pumpkin of ratio:seaweed 58:42), LKRL3 (pumpkin of ratio:seaweed 50:50), LKRL4 (pumpkin of ratio:seaweed 42:58), and LKRL5 (ratio of pumpkin: seaweed 34:66). The data obtained were analyzed statistically using ANOVA. The results showed that the use of yellow squash and seaweed significantly affected water content, ash content, reducing sugar content and sensory rating. The selected treatment from this research was LKRL4 which has moisture content 23.69%, ash content 1.77%, reducing sugar content 8.67% and fiber content 0.88%. While the sensory assessment was descriptive ie brownish, slightly scented pumpkin, sweet taste, chewy texture and favored by panelists. Keywords: Candy jelly, pumpkin and seaweed